2019
DOI: 10.3390/pharmacy7010015
|View full text |Cite
|
Sign up to set email alerts
|

Current Clinical Practice for the Use of Hypnotics to Manage Primary Insomnia in Adults in a Tertiary Hospital in Saudi Arabia: An Audit Study

Abstract: Despite the risks associated with hypnotics and their recent increased use in Saudi Arabia, there are no specific national guidelines for using these medicines to treat insomnia nor are there any data on how these medicines are currently prescribed. There is the potential, however, that some physicians might be adhering to the United States guidelines. The current audit study was aimed to assess the current practice in treating insomnia with hypnotics in Saudi Arabia, and to evaluate its agreement with the US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The findings of this study indicate that patients usually receive sleep medication as a first-line treatment rather than non-pharmacological treatment. This finding is consistent with a previous study by our group indicating that patients in Saudi Arabia are not receiving CBT-I [14], even though it is recommended as initial therapy by many clinical guidelines [19][20][21] and by many experts in Saudi Arabia [22]. This might be due to Saudi physicians' lack of knowledge about non-pharmacological treatment modalities for primary insomnia or their not having the time or expertise to deliver nonpharmacological treatment to patients [15].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The findings of this study indicate that patients usually receive sleep medication as a first-line treatment rather than non-pharmacological treatment. This finding is consistent with a previous study by our group indicating that patients in Saudi Arabia are not receiving CBT-I [14], even though it is recommended as initial therapy by many clinical guidelines [19][20][21] and by many experts in Saudi Arabia [22]. This might be due to Saudi physicians' lack of knowledge about non-pharmacological treatment modalities for primary insomnia or their not having the time or expertise to deliver nonpharmacological treatment to patients [15].…”
Section: Discussionsupporting
confidence: 90%
“…These practices mirror the previous findings of a study conducted in a tertiary hospital in Saudi Arabia showing that around 44% of patients were prescribed antihistamines for primary insomnia. For long-term use, most patients had been prescribed hypnotics, but physicians did not review their patients after initiating this medication [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of national Saudi guidelines for treating primary insomnia, previous work has shown that many physicians follow (or at least consult) United States (US) guidelines, which the Saudi Ministry of Health (MOH) considers to be best practice [26, 27]. An audit, however, of medical records of patients who were prescribed benzodiazepines (BZDs) or Z-drugs (from April 2012 to March 2017 in the same institution as the interview study reported here) compared practice with US guidelines and found that physicians did not actually follow US or international guidelines [28]. Imperatively, further research is needed into the factors that guide diagnostic and treatment practices in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%